PENGGUNAAN BAHASA MELAYU RIAU DAN ORALITY DALAM LINGKUP MASYARAKAT - Aisyah Elvina; Yasnel (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The use of Riau Malay language plays a significant role in preserving cultural identity and communication within local communities. As an integral part of orality traditions, this language functions not only as a communication tool but also as a medium for transmitting cultural values, customs, and history. This study aims to explore the role of the Riau Malay language and oral traditions in fostering social cohesion within the community. The method used is a literature review, examining various academic sources from 2018 to 2024. The findings indicate that Riau Malay language has sustained itself amidst globalization through the revitalization of oral traditions, such as folklore, rhymes, and poetry. This research highlights the importance of preserving local languages to strengthen cultural identity in the modern era.